PEMBERDAYAAN KELOMPOK PEREMPUAN MELALUI PENINGKATAN PRODUK LOKAL DI KECAMATAN SUKARAJA KABUPATEN SELUMA PROVINSI BENGKULU - Hesti Nur'aini; Lina Widawati; Dewi Suranti (Universitas Bengkulu, 2018)
Bukit Peninjauan II and Sido Luhur village are located in Sukaraja Sub District Seluma District Bengkulu Province with low economic growth. The community professions of Bukit Peninjauan II and Sido Luhur village are farmers and construction workers, while the majority of women act as housewives or unskilled laborers, resulting in a relatively low level of community welfare. The purpose of this community service activity is to establish a food processing business unit (carrot sticks, sweet potato sticks, ebi macaroni and sweet potato macaroni, and increasing skills and knowledge of woman group members about food processing). The result of this activity is small business in processing of carrot sticks, sweet potato sticks, sweet potato macaroni and ebi macaroni which is managed by Mawar Melati (Bukit Peninjauan II) and Mandiri Jaya (Sido Luhur), with the trademark Mawar Melati and Bintang Rafflesia. In addition to counseling and production process training, team together with partners also make the formation of packaging and labeling design, the provision of assistance of production tools and the application of marketing methods in the form of blogspot and socialization of small industry financial management.Keywords: local product, woman groups, small business